Hyoid Bone Position and Head Posture in Patients With Richieri-Costa Pereira Syndrome (EIF4A3 Mutations) - Pinto, Rayane de Oliveira [UNESP]; Peixoto, Adriano Porto; Pinto, Ary Dos Santos [UNESP]; Richieri-Costa, Antonio; Raveli, Dirceu Barnabé [UNESP]; Tonello, Cristiano; Dalben, Gisele da Silva (Wolters Kluwer, 2020)
Robin sequence with cleft mandible and limb anomalies, known as Richieri-Costa-Pereira syndrome (RCPS), is an autosomal recessive acrofacial dysostosis characterized by mandibular cleft and other craniofacial anomalies and respiratory complications. The aim of this cross-sectional study was to describe the hyoid and head posture of 9 individuals with RCPS using cephalometric measurements and provide a discussion about its implications in obstructive sleep apnea syndrome (OSAS). The study was conducted on lateral cephalograms of patients with RCPS and 9 selected age-matched controls in tertiary cleft center in Brazil. The cephalograms were digitized and analyzed on a software to obtain the vertical and horizontal hyoid position, its relationship with the mandible and the relation of the cranial base and postvertebral line. The t test was used for analysis of means and Levene's test for equality of variances.Cephalometric measurements H-S (vertical distance between hyoid bone and sella) (Supplemental Digital Content, Figure 1, http://links.lww.com/SCS/B247) and H-C4lp (horizontal position of the hyoid in relation to the post-pharyngeal space) showed statistically significant difference compared to controls (P < 0.05). Therefore, the hyoid bone was more inferiorly and posteriorly positioned in the study group compared with the control group. The vertebrae measurements did not present differences compared to controls. The described position of hyoid bone could be involved in the severe OSAS of RCPS patients.